2016
DOI: 10.1186/s13660-016-1193-y
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvalue bounds of the shift-splitting preconditioned singular nonsymmetric saddle-point matrices

Abstract: For singular nonsymmetric saddle-point problems, a shift-splitting preconditioner was studied in (Appl. Math. Comput. 269:947-955, 2015). To further show the efficiency of the shift-splitting preconditioner, we provide eigenvalue bounds for the nonzero eigenvalues of the shift-splitting preconditioned singular nonsymmetric saddle-point matrices. For real parts of the eigenvalues, the bound is provided by valid inequalities. For eigenvalues having nonzero imaginary parts, the bound is a combination of two inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the section of the numerical experiments, we choose the matrix Q as Q = αI + βBB T where β > 0. In this case, when α, β → 0 we deduce that n eigenvalues of the preconditioned matrix are approximately equal to 1 and from (23) it follows that the others tends to 0 or 1.…”
Section: Solve (H +mentioning
confidence: 83%
See 1 more Smart Citation
“…In the section of the numerical experiments, we choose the matrix Q as Q = αI + βBB T where β > 0. In this case, when α, β → 0 we deduce that n eigenvalues of the preconditioned matrix are approximately equal to 1 and from (23) it follows that the others tends to 0 or 1.…”
Section: Solve (H +mentioning
confidence: 83%
“…In [18], Ren et al investigated the eigenvalue distribution of the shift-splitting preconditioned saddle point matrix and showed that all eigenvalues having nonzero imaginary parts are located in an intersection of two circles and all real eigenvalues are located in a positive interval. Shi et al in [23] provided eigenvalue bounds for the nonzero eigenvalues of the shift-splitting preconditioned singular nonsymmetric saddle point matrices.…”
Section: Introductionmentioning
confidence: 99%
“…(b) When A is PD, the P GSS preconditioner was studied in [16,17,34,36,38] and P ESS preconditioner was studied in [35].…”
Section: Semi-convergence Of Epss Iteration Methodsmentioning
confidence: 99%
“…Theoretical analysis shows that the stationary iteration method (1.5) for saddle point problems is unconditionally convergent. For saddle point problems with a Hermitian positive definite (1, 1) block matrix, the spectral properties of the shift-splitting preconditioned matrix are discussed in [37,44]. A generalised shift-splitting preconditioner with an additional parameter β has been studied in [23,24,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…A generalised shift-splitting preconditioner with an additional parameter β has been studied in [23,24,[41][42][43]. Numerical results suggest that the shift-splitting preconditioner SS and its generalisations are efficient in saddle point problems of computational fluid dynamics [22][23][24]44] and in meshfree discretisations of elasticity problems [37]. However, for time-harmonic current eddy models there are implementation difficulties associated with special block structure of the non-Hermitian saddle point matrix in (1.3).…”
Section: Introductionmentioning
confidence: 99%